2013
DOI: 10.1016/j.contraception.2012.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Women's preferences for contraceptive counseling and decision making

Abstract: Background Little is known about what women value in their interactions with family planning providers and in decision making about contraception. Study Design We conducted semistructured interviews with 42 black, white and Latina patients. Transcripts were coded using modified grounded theory. Results While women wanted control over the ultimate selection of a method, most also wanted their provider to participate in the decision-making process in a way that emphasized the women’s values and preferences. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
210
2
15

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 239 publications
(235 citation statements)
references
References 34 publications
8
210
2
15
Order By: Relevance
“…The patient-reported Interpersonal Quality in Family Planning care (IQFP) scale was developed for this study using a review of domains related to patientcentered care included in patientreported quality measures, 9-14 previous qualitative work on women's preferences for contraceptive counseling, 15 and factor analysis. Originally, 17 items were included in the postvisit survey encompassing all identified domains related to patient-centered care.…”
Section: Methodsmentioning
confidence: 99%
“…The patient-reported Interpersonal Quality in Family Planning care (IQFP) scale was developed for this study using a review of domains related to patientcentered care included in patientreported quality measures, 9-14 previous qualitative work on women's preferences for contraceptive counseling, 15 and factor analysis. Originally, 17 items were included in the postvisit survey encompassing all identified domains related to patient-centered care.…”
Section: Methodsmentioning
confidence: 99%
“…Receiving such reactions to their actions and wishes can lead to changes in their expectations of further counselling. Previous studies (Dehlendorf et al 2013;Donnelly et al 2014;Jaccard and Levitz 2013) have taken note of the problematic situation women are put in when they do not view their caregivers as accommodating, and, as the present study has shown, there may be many negative consequences. It could, for example, lead to an experience of being unable to make a meaningful choice, and, thus, result in the choice of not returning for further consultations.…”
Section: Discussionmentioning
confidence: 82%
“…International research (e.g., Dehlendorf et al 2017), as well as midwife advisory literature (Kaplan 2009), also emphasises that caregivers should provide opportunities to discuss the client's requests, and enable the establishment of trust in the caregiver. Several studies further point to a connection between women's consistency of use and how they perceived the counselling given (Dehlendorf et al 2013;Donnelly et al 2014;Sköld and Larsson 2012). Caregivers could, in other words, have a very large influence on the contraceptive choice made, as well as the consistency of contraceptive use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On one hand, as contraceptive counseling addresses profoundly personal issues related to sexuality and fertility, it has been suggested that there is value to intimacy in the provider-patient relationship, which would support the value of PSD [12,13]. Additionally, PSD might strengthen the legitimacy of information given by the provider, as studies have found that patients value information obtained through personal experiences of contraception [12,14,15]. On the other hand, the concern remains that PSD may be perceived as, or in fact be, inappropriate or even coercive [16].…”
Section: Introductionmentioning
confidence: 99%